Pengaruh Penambahan Bubuk Jahe Emprit (Zingiber officinale var. Amarum) Terhadap Karakteristik Teh Celup Herbal Daun Salam (Syzygium polyanthum (Wight.) Walp) - Jasmine Chandra Dewi, Ida Ayu Putu; Timur Ina, Putu; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPA, 2021)
This research was aimed to determine the effect of the emprit ginger powder additions on the characteristics of bay leaf herbal tea bag and to determine the appropriate addition of emprit ginger powder to get the best bay leaf herbal tea bag characteristics. The design used in this study was a Completely Randomized Design (CRD) with an additional emprit ginger powder treatment with consisting of 5 namely: 0%, 5%, 10%, 15%, and 20%. This study was repeated 3 times so that they were obtained 15 experimental units. The data obtained were analyzed by analysis of variance (ANOVA) and if the treatment had a significant effect followed by Duncan’s Multiple Range Test (DMRT). The results showed that the addition of 20% emprit ginger powder had a significant effect (P<0,05) on moisture content, extract content in water, phenol total, flavonoid total, antioxidant activity, IC50, hedonic test and scoring test (aroma and taste). The results showed that bay leaf herbal tea bag with the addition of 20% emprit ginger powder was the best treatment with moisture content 8.93%, extract content in water 16.97%, phenol total 3.35 mgGAE/g, flavonoid total 0.62 mgQE/g, antioxidant activity 73.90%, IC50 value 640.99 ppm. The characteristics of the brewed tea water such as the color was common, the typhical aroma of emprit ginger and liked, the typhical taste of emprit ginger and liked, and overall acceptance was liked.